HAND WASHING BEHAVIOR WITH SOAP (CTPS) IN ELEMENTARYSCHOOLSTUDENTS IN 2020 (STUDY OF LITERATURE) - Muhammad Zaid; Zubir (Aceh Sanitation Journal, 2022)
The background of washing hands using soap has become one of the movements launched by the government. Washing hands with soap is able to reduce diarrhea rates by as much as 45%, but the use of soap for hand washing only reaches about 3% of all people who use soap to wash their hands. The study aimed to determine the behavior that affects hand washing with soap (CTPS) in elementary school students. This type of research uses qualitative research which is library research on the behavior of washing hands with soap (ctps) in elementary school students. The results of the research on the knowledge of hand washing with soap in elementary school students there is a Good Knowledge of 50.8%. bad knowledge 49.2%, the attitude of washing hands with soap in elementary school students there is good behavior Washing hands is 44%, bad behavior washing hands is 56%, washing hands with soap in elementary school students there are 51.2% respondents, behavior The factors that affect hand washing with soap (CTPS) in elementary school students can be seen from parenting patterns, understanding of educational media, the role of teachers, the role of health workers and the availability of ctps facilities in elementary schools.The conclusion from the overall results of the study by analyzing several journals is that there is an effect of washing hands with soap (CTPS) on elementary school students.